2016
DOI: 10.4314/jasem.v20i3.1
|View full text |Cite
|
Sign up to set email alerts
|

Use of bentonite clay for the reduction of cyanide poisoning after consumption of cassava waste water by Wistar albino rat

Abstract: ABSTRACT:The in vivo study of the effect of bentonite on cyanide poisoning and its effect on plasma urea was investigated. A total of 45 wistar albino rats were used. The rats were divided into four groups and a control group. Each group had nine rats including the control. Groups 1, 2, 3, and 4 were given a daily dose of 0.4ml of cassava waste water containing a sub-lethal amount of cyanide (2.16 x 10 -3 mg). Groups 2, 3, and 4 were counter administered with 0.2ml, 0.4ml, and 0.8ml of 7% bentonite solution re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Furthermore, some other studies showed also that bentonite has the ability to protect birds and other animals to some extent against the hepatoxicity of Aflatoxins [26,27,28,29]. Similarly, a recent study by Okoye and Uwhen, [1] stipulated that cyanide exposure caused a significant increase in the plasma urea level and that bentonite administration was effective in mitigating the resultant alteration. They suggested that bentonite might have some preventive and therapeutic effects on cyanide poisoning.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, some other studies showed also that bentonite has the ability to protect birds and other animals to some extent against the hepatoxicity of Aflatoxins [26,27,28,29]. Similarly, a recent study by Okoye and Uwhen, [1] stipulated that cyanide exposure caused a significant increase in the plasma urea level and that bentonite administration was effective in mitigating the resultant alteration. They suggested that bentonite might have some preventive and therapeutic effects on cyanide poisoning.…”
Section: Discussionmentioning
confidence: 99%
“…Bentonite has been found to be effective in counteracting toxins [1,2]. However, the ability of bentonite to bind these toxins depends on pH, molecular arrangements, and its geographic region of origin [3,4,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation